SPATIAL PATTERN OF STUNTING ON CHILDREN UNDER FIVE IN INDONESIA 2019 - Minsarnawati Tahangnacca; Fika Muntahaya (IAKMI South Tangerang Branch, 2022)
Abstract Background: The stunting countermeasures is one of the agendas in SDGs. The strategic and appropriate attempts could be planned based on the distribution of stunting and the influencing factors using a region-based data approach in accordance with the critical steps within the 2018 Global Nutrition Report. Objective: The purpose of this study was to determine the spatial autocorrelation of stunting on children under five between districts/cities in Indonesia 2019. Method: This research is an ecological study using a spatial approach. The data used was secondary data obtained from the study of Nutritional Status of children in 2019, with the unit of analysis for all districts/cities in Indonesia. The study was tested using the analysis of Global Moran’s I and Local Indicators of Spatial Association (LISA). Result: The result of the analysis showed that stunting on children under five between districts/cities in Indonesia has a spatial autocorrelation with a clustered pattern (I=0.347). Conclusion: Areas with high-high stunting patterns need to be set as priority areas for stunting reduction interventions. In addition, the formation of a Stunting Reduction Acceleration Team in these areas needs to be monitored thoroughly.